Asymmetric Microtubule Function Is an Essential Requirement for Polarized Organization of the Drosophila Bristle - Bitan, Amir (American Society for Microbiology (ASM), 2010)
While previous studies have shown that microtubules (MTs) are essential for maintaining the highly biased axial growth of the Drosophila bristle, the mechanism for this process has remained vague. We report that the MT minus-end marker, Nod-KHC, accumulates at the bristle tip, suggesting that the MT network in the bristle is organized minus end out. Potential markers for studying the importance of properly polarized MTs to bristle axial growth are Ik2 and Spindle-F (Spn-F), since mutations in spn-F and ik2 affect bristle development. We demonstrate that Spn-F and Ik2 are localized to the bristle tip and that mutations in ik2 and spn-F affect bristle MT and actin organization. Specifically, mutation in ik2 affects polarized bristle MT function. It was previously found that the hook mutant exhibited defects in bristle polarity and that hook is involved in endocytic trafficking. We found that Hook is localized at the bristle tip and that this localization is affected in ik2 mutants, suggesting that the contribution of MTs within the bristle shaft is important for correct endocytic trafficking. Thus, our results show that MTs are organized in a polarized manner within the highly elongated bristle and that this organization is essential for biased bristle axial growth.